Shomei Tomatsu : Skin of the nation. - SFMOMA (San Francisco Museum of Modern Art) San Francisco; Corcoran Gallery of Art Washington; Fotomuseum Winterthur; Japan Society Gallery New York; Benezra, Neal; Dower, John W.; Moriyama, Daido; Phillips, Sandra S.; Rubinfien, Leo (London; New Haven; San Francisco : SFMOMA (San Francisco Museum of Modern Art) San Francisco : Yale University Press London : Yale University Press New Haven, 2004)
Published on the occasion of a major traveling exhibition organized by the San Francisco Museum of Modern Art in association with Japan Society New York, this catalogue - the first comprehensive publication on Tomatsu to appear in English - includes essays addressing his fifty year career, his artistic influences, and his historical context. A selection of excerpts from Tomatsu's own writings, many of which have never appeared in English, offers an intimate encounter with the issues and themes addressed in his photographs.
bibliog. p. 214-216
biog. p. 212-213, tent. p. 213-214
Engels
Exhibition. Shomei Tomatsu : Skin of the nation. Corcoran Gallery of Art Washington. Fotomuseum Winterthur. Japan Society Gallery New York. SFMOMA (San Francisco Museum of Modern Art) (2004-2006)
boek
Keywords: Tomatsu, Shomei